Testing Metaphorical Educational FPS Games - John R. Rankin; Sandra Sampayo Vargas; Paul F. Taylor (International Journal of Computer Games Technology)
It is widely recognized that there is value in making use of modern Games Technology in Serious Games for educational purposes in the classroom and yet tools that enable teachers to construct such Educational Serious Games (ESGs) with minimal programming, artistic, or GT skills are not yet widely available. In this paper we investigate the feasibility of employing the FPS game genre for teaching purposes in the classroom. This is done by starting with a typical FPS game and constructing metaphorical correspondences with the desired ESG category. This mapping highlights the mentality level of FPS games and what it would take to modify them towards the level for real knowledge acquisition as in ESGs. By changing the game world rules to correspond with a classroom study area, we create a metaphorical educational FPS game. In this paper we describe two metaphorical educational FPS games and report on preliminary testing of their use in education. If testing of these metaphorical educational FPS games indicates that they would be beneficial in school classes then we intend to pursue the design of software tools and tutorials to enable teachers to develop their own metaphorical educational FPS games in two months or less.